2011
DOI: 10.1007/s00421-011-2143-5
|View full text |Cite
|
Sign up to set email alerts
|

The intraocular pressure response to dehydration: a pilot study

Abstract: The aim of this study was to determine the intraocular pressure response to differing levels of dehydration. Seven males participated in 90 min of treadmill walking (5 km h(-1) and 1% grade) in both temperate (22 °C) and hot (43 °C) conditions. At baseline and 30 min intervals intraocular pressure, nude body mass, body temperature and heart rate were recorded. Statistically significant interactions (p < 0.05) were observed for intraocular pressure (hot condition: baseline 17.0 ± 2.9, 30 min 15.6 ± 3.5, 60 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…decreases in hydration status) took place during higher temperatures and with prolonged exercise because the hypotonic fluid losses via sweating were greater. While this was a small pilot study, a moderate correlation between decline in IOP and decline in hydration status (adjusted r 2 = 0.51) was found, suggesting IOP progressively decreases with progressive dehydration . However, an older study is noteworthy in which participants were subjected to graded exercise to exhaustion (with and without additional CO 2 inhalation for isocapnia) over 19–22 min (excluding two periods of 2 min rest) and fixed intensity exercise for 10 min, all on separate occasions.…”
Section: Search Strategymentioning
confidence: 88%
See 1 more Smart Citation
“…decreases in hydration status) took place during higher temperatures and with prolonged exercise because the hypotonic fluid losses via sweating were greater. While this was a small pilot study, a moderate correlation between decline in IOP and decline in hydration status (adjusted r 2 = 0.51) was found, suggesting IOP progressively decreases with progressive dehydration . However, an older study is noteworthy in which participants were subjected to graded exercise to exhaustion (with and without additional CO 2 inhalation for isocapnia) over 19–22 min (excluding two periods of 2 min rest) and fixed intensity exercise for 10 min, all on separate occasions.…”
Section: Search Strategymentioning
confidence: 88%
“…While this was a small pilot study, a moderate correlation between decline in IOP and decline in hydration status (adjusted r 2 = 0.51) was found, suggesting IOP progressively decreases with progressive dehydration. 47 However, an older study 59 is noteworthy in which participants were subjected to graded exercise to exhaustion (with and without additional CO2 inhalation for isocapnia) over 19-22 min (excluding two periods of 2 min rest) and fixed intensity exercise for 10 min, all on separate occasions. The IOP declined relative to sedentary controls during the trial, but because the plasma osmolarity was equal to, or slightly lower than baseline after exercise, no correlation between IOP and plasma osmolarity was found, indicating the hydration status of the participants did not change during the trial.…”
Section: -55mentioning
confidence: 99%
“…A common practice among endurance riders is to provide electrolytes, beet pulp, and other modalities to encourage hydration prior to a ride to improve equine metabolic status during a ride and prevent dehydration. These techniques may result in over hydration and affect baseline IOP in the opposite manner as that proposed with dehydration and IOP reduction …”
Section: Discussionmentioning
confidence: 99%
“…Three leading theories include decreased blood pH, elevated blood lactate, or elevated plasma osmolarity, with the latter being most supported by current literature and the only one present in aerobic as well as anaerobic exercise . Several studies have reported that dehydration causes an increase in plasma osmolality, which in turn may lower the rate of aqueous humor formation and result in documented IOP reduction through osmotic dehydration of the globe, reduced aqueous ultrafiltration, or a hypothalamic reflex …”
Section: Introductionmentioning
confidence: 97%
“…V˙O 2max and maximum heart rate were determined as per standard laboratory procedure [9]. Following a warm up period, participants determined a comfortable running speed for use during the test.…”
Section: Methodsmentioning
confidence: 99%